X線回折法による軟膏中の主成分の定量(第3報) : 軟膏中のサリチル酸, アミノ安息香酸エチルおよびスルフイソミジンの定量 - 黒田, 耕司; 橋詰, 源蔵 (YAKUGAKU ZASSHI, 1967)
Determination of the chief components in an ointment was carried out on various ointments having white petrolatum as the base and containing salicylic acid, ethyl aminobenzoate, and/or sulfisomidine, employing the X-ray diffraction by the direct method and by the internal standard method using magnesium oxide as the standard. The mass absorption coefficient, μ, of these main components is approximately the same as that of the base, and the concentration of the chief component and intensity of the diffraction lines in the direct method were approximately linear. Determination of these ointments by the X-ray diffraction method seems to be practicable.